Will Haiti benefit from setting up an agricultural research center? A foresight quantification - Bairagi, Subir; Durand-Morat, Alvaro (Emerald Publishing Limited, 2020)
Investments in agricultural research and development (AgR&D) have been an engine of agricultural productivity growth; as a result, food security and poverty situations have improved in many countries around the world. However, in Haiti, a small Caribbean country, neither has any formal agricultural research center (ARC) been established nor has a significant amount of money been invested for AgR&D. This paper aims to quantify whether setting up an ARC would be beneficial for Haiti.A fixed-effects regression, the International Model for Policy Analysis of Agricultural Commodity and Trade impact and benefit – cost ratio (BCR) measures are used to estimate future benefits from setting up a new ARC in Haiti.A total of US$21.0m annual investment is required for the proposed ARC, which could generate up to US$1.16bn in social benefits during the next three decades. In terms of BCR, if one dollar is invested for AgR&D in Haiti, the payoff could be US$1.33-4.52. Therefore, establishing an ARC is crucial for Haiti, as it is expected to generate positive benefits for society by helping formulate pro-farmer policies as well as disseminating modern agricultural technologies among farmers.Because, to the best of the authors’ knowledge, there is no such study in Haiti’s perspective, this study contributes to the country’s literature evaluating the feasibility of establishing a new research center in Haiti with a partial equilibrium economic model.